Kepemimpinan KH Sahal Mahfudh di Lembaga Pendidikan Islam: Analisis SWOT - Ahmad Muchlishon (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to analyze the educational leadership patterns of KH MA Sahal Mahfudh (Kiai Sahal) at three Islamic institutions: Pesantren Maslakul Huda (PMH) Kajen, Pati, Perguruan Islam Mathali’ul Falah (PIM) Kajen, Pati,, and Universitas Nahdlatul Ulama (UNISNU) Jepara. The research uses a qualitative method, combining library research with field research through interviews and observations. Data were analyzed using the SWOT (Strengths, Weaknesses, Opportunities, Threats) framework with historical and sociological approaches. The results show that Kiai Sahal implemented a collective-participatory-transformational leadership style, breaking the tradition of centralized kiai authority by delegating power to subordinates. Crucial policies include the formation of the Pesantren-Owned Business Entity (BUMP) for financial independence at PMH, the consistency of the